Brand localization and consumer perception in China: A pavlovian conditioning approach - Siregar, Sheyla Silvia; Prabumeang, Agung Krisnamurti; Pratamasari, Dewi Agustin (Priviet Social Sciences Journal, 2025)
Globalization has driven international companies to adapt their brand strategies to local markets, particularly in China, which has become one of the world’s largest and most dynamic economies. One crucial aspect of this adaptation is brand name localization, where international brands translate their names into Mandarin to ensure linguistic familiarity, cultural relevance, and positive perceptions. This study examines consumer perceptions of localized brand names—Burger King (汉堡王), KFC (肯德基), and Starbucks (星巴克)—by integrating the theoretical perspective of Pavlovian conditioning with international marketing strategies. A survey of 500 respondents was conducted to measure consumer attitudes toward dimensions such as memorability, cultural appropriateness, emotional resonance, and the influence on purchase decisions. The findings indicate that local brand names significantly shape consumer perceptions and purchasing behavior. Starbucks (星巴克) was perceived as the most successful brand name, associated with coffee culture, a premium lifestyle, and ease of recall. KFC (肯德基) was found to evoke positive emotions strongly, while Burger King (汉堡王) was more likely to trigger curiosity rather than a strong cultural association with Western fast food. Repetition of brand names also enhances positive consumer emotions, aligning with Pavlovian conditioning, where repeated stimuli strengthen affective responses. This study contributes to the understanding of brand localization as a strategic marketing tool in cross-cultural contexts. The results highlight the importance of phonological adaptation, cultural alignment, and consistent brand communication in building consumer trust and loyalty in international markets, particularly in China.